Cardiac defects of hypermobile Ehlers-Danlos syndrome and hypermobility spectrum disorders: a retrospective cohort study - Knight, Dacre R. T.; Bruno, Katelyn A.; Singh, Ayush; Munipalli, Bala; Gajarawala, Shilpa; Solomon, Mahima; Kocsis, S. Christian; Darakjian, Ashley A.; Jain, Angita; Whelan, Emily R.; Kotha, Archana; Gorelov, David J.; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Defective connective tissue structure may cause individuals with hypermobile Ehlers-Danlos syndrome (hEDS) or hypermobility spectrum disorders (HSD) to develop cardiac defects. Methods: We conducted a retrospective chart review of adult patients treated in the EDS Clinic from November 1, 2019, to June 20, 2022 to identify those with cardiac defects. Echocardiogram data were collected using a data collection service. All EDS Clinic patients were evaluated by a single physician and diagnosed according to the 2017 EDS diagnostic criteria. Patient demographic, family and cardiac history were extracted from self-reported responses from a REDCap clinical intake questionnaire. Patients with at least 1 available echocardiogram (ECHO) were selected for the study (n = 568). Results: The prevalence of aortic root dilation in patients with hEDS was 2.7% and for HSD was 0.6%, with larger measurements for males than females and with age. Based on selfreported cardiac history that was verified from the medical record, patients with hEDS with bradycardia (p = 0.034) or brain aneurysm (p = 0.015) had a significantly larger average adult aortic root z-score. In contrast, patients with HSD that self-reported dysautonomia (p = 0.019) had a significantly larger average aortic root z-score. The prevalence of diagnosed mitral valve prolapse in patients with hEDS was 3.5% and HSD was 1.8%. Variants of uncertain significance were identified in 16 of 84 patients that received genetic testing based on family history. Conclusions: These data reveal a low prevalence of cardiac defects in a large cohort of well-characterized hEDS and HSD patients. Differences in cardiovascular issues were not observed between patients with hEDS versus HSD; and our findings suggest that cardiac defects in patients with hEDS or HSD are similar to the general population.